Highly permeable aramid-coated separator and process for its preparation
Patent Information
- Application Number
- CN202310921579.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-07-24
AI Technical Summary
[0004]目前,大规模商业化的隔膜材料主要以聚乙烯、聚丙烯为主,但此类材料熔点较低,当电池内部升高到一定温度时,隔膜很难保持其原有尺寸,导致正负极短路
芳纶分子与聚乙烯醇分子之间具有广泛的氢键结合,两者之间高节点连接性和原分子之间的牢固连接会形成具有高机械强度的网状结构,使隔膜具有更好的热稳定性。该网状结构在具备较高强度的同时,还具有丰富孔结构。高机械强度赋予涂层较好抗穿刺能力,孔状结构使芳纶涂层保持较好电解液亲和力的同时具有较高保液率。此外,制备的芳纶涂覆隔膜具有更好的透气性。
Smart Images

Figure CN116722304B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of advanced inorganic non-metallic materials and core electronic industry technology, and relates to core materials for battery cells, especially components of lithium-ion batteries, specifically a high-permeability aramid coated separator and its preparation process. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] As one of the four main materials of lithium-ion batteries, the separator not only provides lithium-ion channels but also separates the positive and negative electrodes, preventing short circuits caused by contact between them. It is crucial for ensuring the safety performance of lithium-ion batteries. With the upgrading of battery systems, the heat generated by the cells under operating conditions increases. To prevent internal short circuits and thermal runaway, the safety of each battery component must be further improved.
[0004] Currently, commercially available separator materials are mainly polyethylene and polypropylene. However, these materials have low melting points, and when the internal temperature of the battery rises to a certain level, the separator struggles to maintain its original dimensions, leading to short circuits between the positive and negative electrodes. To improve this situation, a common method is to coat these separators with ceramics or organic materials to enhance their thermal stability. However, with the upgrading of battery material systems and the increasing demands for battery safety, ceramic / organic coated separators exhibit poor heat resistance in higher temperature ranges (T > 150℃). Moreover, ceramic / organic coated separators can lead to a decrease in the lithium-ion permeability of the separator. Therefore, selecting a separator that significantly improves the heat resistance of lithium battery separators is a pressing issue that needs to be addressed. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the purpose of this invention is to provide a high-permeability aramid-coated separator and its preparation process.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a process for preparing a highly permeable aramid-coated separator, comprising the following steps: Aramid solution and polyvinyl alcohol solution are mixed evenly to carry out mixed modification. The mass ratio of aramid to polyvinyl alcohol is 1:1-5. During the mixing process, the amide groups on the aramid nanofiber molecules, the hydroxyl groups on the polyvinyl alcohol molecules, and the hydroxyl groups on the water molecules form strong hydrogen bonds with each other and establish an interconnected polymer network. The mixing and modification temperature is 10-30℃ and the mixing and modification time is 20-60min. The molecular weight of the polyvinyl alcohol is 146,000-186,000; After the mixing and modification are completed, defoamer and binder are added, and the mixture is mixed evenly to obtain the coating slurry; The coating slurry is applied to one or both sides of the diaphragm, dried, and then subjected to solvent exchange in a pure water bath before being dried completely.
[0007] Aramid fiber molecules, as nanopolymers, have abundant linkage points, and the inherent branching of the molecules also contributes to the high connectivity of the network structure. The extensive hydrogen bonds between aramid molecules and polyvinyl alcohol enable the two molecules to crosslink relatively easily. The crosslinked network structure has high mechanical strength while providing a large number of porous channels for lithium ions, and the coating process does not reduce the lithium ion permeability of the substrate.
[0008] During the mixing process, the amide groups on the aramid nanofiber molecules, the hydroxyl groups on the polyvinyl alcohol molecules, and the hydroxyl groups on the water molecules form strong hydrogen bonds with each other and establish an interconnected polymer network. The mixing and modification temperature is 10-30℃. If the mixing temperature is too low or too high, it will affect the local dispersion uniformity of the two fibers, thereby reducing the strength of the composite fiber. The mixing and modification time is 20-60 min. The molecular weight of the polyvinyl alcohol is 146,000-186,000, which is a high degree of polymerization polyvinyl alcohol. Within this range, the viscosity of the polyvinyl alcohol solution is moderate, which is conducive to processing and also helps to improve the strength and elongation of the fiber after composite. As the degree of polymerization of polyvinyl alcohol increases, the viscosity of the aqueous solution increases, and the strength and solvent resistance of the film after formation are improved, but the solubility in water and the elongation after film formation decrease.
[0009] In some embodiments, the concentration of the aramid solution is 1-5 wt%.
[0010] Preferably, the aramid solution contains a co-solvent selected from one or a combination of lithium chloride (LiCl), calcium chloride (CaCl2), or calcium hydroxide (Ca(OH)2).
[0011] Preferably, the solvent of the aramid solution is one or a combination of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP) or dimethyl phthalate (DMP).
[0012] In some embodiments, the concentration of the polyvinyl alcohol solution is 1-10 wt%.
[0013] Preferably, the degree of alcoholysis of the polyvinyl alcohol is 99%.
[0014] Preferably, the solvent for polyvinyl alcohol is dimethyl sulfoxide (DMSO).
[0015] In some embodiments, the defoamer is one or a combination of diethylhexanol, n-octanol, isooctanol, or isoamyl alcohol.
[0016] In some embodiments, the adhesive is a polyacrylic resin, polyvinyl acetate, or ethylene-vinyl acetate copolymer.
[0017] In some embodiments, the diaphragm is a polyethylene diaphragm, a polypropylene diaphragm, or a polyamide diaphragm.
[0018] Secondly, the present invention provides a highly permeable aramid-coated separator, which is prepared by the aforementioned preparation process.
[0019] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: Extensive hydrogen bonding exists between aramid and polyvinyl alcohol molecules. The high nodal connectivity between them and the strong bonds between the original molecules form a network structure with high mechanical strength, resulting in better thermal stability of the membrane. This network structure possesses both high strength and abundant pores. The high mechanical strength imparts good puncture resistance to the coating, while the porous structure allows the aramid coating to maintain good electrolyte affinity and high electrolyte retention. Furthermore, the prepared aramid-coated membrane exhibits better air permeability.
[0020] Porosity can be adjusted by adjusting the slurry concentration, which reduces the impact of coating on lithium-ion permeability and improves the performance of the separator under high-rate conditions. Attached Figure Description
[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0022] Figure 1 This is a schematic diagram illustrating the aramid modification principle of the present invention; Figure 2 This is a comparison image of SEM images of the Al2O3 ceramic coated membrane (a) and the aramid coated membrane prepared in Example 1 (b). Figure 3 These are comparison images of the diaphragm before and after heating in the embodiments of the present invention and Comparative Example 1. Detailed Implementation
[0023] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0024] The present invention will be further described below with reference to the embodiments.
[0025] The molecular weight of polyvinyl alcohol used in the following examples is 146,000-186,000.
[0026] Example 1 Aramid fibers (PPTA) were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide. After stirring and mixing, a 1 wt% aramid solution was prepared for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0027] A certain amount of polyvinyl alcohol was added to dimethyl sulfoxide solvent and mixed by stirring to prepare a 1wt% polyvinyl alcohol solution. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0028] Aramid solution and polyvinyl alcohol solution were mixed and modified at a mass ratio of aramid to polyvinyl alcohol of 1:2. The mixing temperature was T=30℃, n=200rpm, and t=60min.
[0029] After modification, add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0030] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0031] like Figure 1 As shown in the figure, electron microscopy after coating reveals that the cross-linking of polyvinyl alcohol and aramid fibers forms a network structure on the membrane surface, and the linking points in the molecular chains are clearly visible under the electron microscope. Furthermore, the aramid-polyvinyl alcohol composite network structure has a larger pore size compared to the membrane substrate, therefore, the aramid coating does not reduce the lithium-ion permeability.
[0032] Example 2 Aramid fibers were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide, and stirred to prepare a 4wt% aramid solution for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0033] A certain amount of polyvinyl alcohol was added to dimethyl sulfoxide solvent and mixed by stirring to prepare a 4wt% polyvinyl alcohol solution. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0034] Aramid solution and polyvinyl alcohol solution were mixed and modified at a mass ratio of aramid to polyvinyl alcohol of 1:2. The mixing temperature was T=30℃, n=200rpm, and t=60min.
[0035] After modification, add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0036] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0037] Example 3 Aramid fibers were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide, and stirred to prepare an 8wt% aramid solution for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0038] A certain amount of polyvinyl alcohol was added to dimethyl sulfoxide solvent and mixed by stirring to prepare an 8wt% polyvinyl alcohol solution. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0039] Aramid solution and polyvinyl alcohol solution were mixed and modified at a mass ratio of aramid to polyvinyl alcohol of 1:2. The mixing temperature was T=30℃, n=200rpm, and t=60min.
[0040] After modification, add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0041] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0042] Comparative Example 1 1. Mix 25%~70% polyethylene resin, 1%~5% boehmite, and 30~70% paraffin oil, then melt-blend the mixture in an extruder and extrude it through a die. The mixing temperature T = 180℃~220℃, and the stirring speed n = 90~120 rpm. The viscosity-average molecular weight of the polyethylene resin is 900,000~3,000,000.
[0043] 2. The sheet from step 1 is subjected to biaxial stretching at a temperature of 180℃~220℃ and a stretching ratio of 6~10 times.
[0044] 3. Immerse the material from step 2 in dichloromethane for extraction, and then dry it. The extraction temperature is room temperature, and the drying temperature is 40℃.
[0045] 4. The material from step 3 is subjected to biaxial stretching and shaping at a stretching temperature of 180℃~220℃ and a stretching ratio of 5~10 times. The shaping temperature is 120~150℃.
[0046] 5. Preparation of coating slurry: Add 35% Al2O3, 1% sodium dodecyl sulfonate dispersant, and 5% sodium carboxymethyl cellulose to deionized water and stir to prepare an alumina slurry for later use. Mixing temperature T=55℃, stirring speed n=300rpm, stirring time t=50min.
[0047] 6. The coating slurry from step 5 is evenly dispersed on one or both sides of the diaphragm using a gravure roller or rotary nozzle device via roller coating or spraying. Finally, it is dried in an oven. The pre-drying temperature is T=95℃, and the coating thickness is 3μm.
[0048] 7. Roll up the material from step 6.
[0049] Comparative Example 2 The difference from Example 1 is that the steps of preparing the polyvinyl alcohol solution and the steps of using the polyvinyl alcohol solution to mix and modify the aramid are omitted; otherwise, they are the same as in Example 1.
[0050] Aramid fibers (PPTA) were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide. After stirring and mixing, a 1 wt% aramid solution was prepared for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0051] Add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0052] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0053] Comparative Example 3 The difference from Example 1 is that the molecular weight of the polyvinyl alcohol used is 10,000-14,000, while all other aspects are the same as in Example 1.
[0054] The polyvinyl alcohol used in this embodiment has a molecular weight of 10,000-14,000; Aramid fibers (PPTA) were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide. After stirring and mixing, a 1 wt% aramid solution was prepared for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0055] A certain amount of polyvinyl alcohol was added to dimethyl sulfoxide solvent and mixed by stirring to prepare a 1wt% polyvinyl alcohol solution. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0056] Aramid solution and polyvinyl alcohol solution were mixed and modified at a mass ratio of aramid to polyvinyl alcohol of 1:2. The mixing temperature was T=30℃, n=200rpm, and t=60min.
[0057] After modification, add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0058] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0059] Comparative Example 4 The difference from Example 1 is that the molecular weight of the polyvinyl alcohol used is 18,600-20,000, while all other aspects are the same as in Example 1.
[0060] The molecular weight of the polyvinyl alcohol used in this embodiment is 18,600-20,000; Aramid fibers (PPTA) were added to a mixed solution of solvent dimethyl sulfoxide and co-solvent calcium hydroxide. After stirring and mixing, a 1 wt% aramid solution was prepared for later use. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0061] A certain amount of polyvinyl alcohol was added to dimethyl sulfoxide solvent and mixed by stirring to prepare a 1wt% polyvinyl alcohol solution. The mixing temperature was T=75℃, the stirring speed was n=250rpm, and the stirring time was t=45min.
[0062] Aramid solution and polyvinyl alcohol solution were mixed and modified at a mass ratio of aramid to polyvinyl alcohol of 1:2. The mixing temperature was T=30℃, n=200rpm, and t=60min.
[0063] After modification, add 0.75wt% octanol solution as defoamer and 0.25wt% polyacrylate solution as binder, and continue stirring and mixing. After mixing, a coating slurry is prepared.
[0064] The above-mentioned coating slurry was gravure-coated onto one side of a polyethylene diaphragm using a roller. After pre-drying in an oven, solvent exchange was performed in a pure water bath, followed by final oven drying. The pre-drying temperature was T=80~100℃, and the oven temperature was T=90~105℃. The coating thickness for both roller coating and spray coating was 2μm.
[0065] Comparing the results before and after heating (180℃, 1h), it can be found that, compared with the traditional Al2O3 ceramic coated membrane, the aramid coated membranes with three different ratios exhibit better heat resistance and dimensional stability under the same heating conditions.
[0066] Table 1. Performance Comparison of Examples and Comparative Examples
[0067] As shown in Table 1, this method can adjust the coating porosity while maintaining the coating tensile strength by adjusting different ratios. Compared with traditional Al2O3 ceramic coating, the aramid-coated separator obtained by this method exhibits better air permeability and is more suitable for high-rate battery operation. Furthermore, in terms of thermal shrinkage, the aramid-coated separator demonstrates better thermal stability, resulting in better battery safety.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A process for preparing a high-permeability aramid-coated separator, characterized in that: Includes the following steps: Aramid solution and polyvinyl alcohol solution are mixed evenly to carry out mixed modification. The mass ratio of aramid to polyvinyl alcohol is 1:1-5. The temperature for mixing and modification is 10-30℃, and the time for mixing and modification is 20-60 min; The molecular weight of the polyvinyl alcohol is 146,000-186,000; After the mixing and modification are completed, defoamer and binder are added, and the mixture is mixed evenly to obtain the coating slurry; The coating slurry is applied to one or both sides of the diaphragm, dried, and then subjected to solvent exchange in a pure water bath before being dried completely.
2. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The concentration of the aramid solution is 1-5 wt%.
3. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The aramid solution contains a co-solvent, which is selected from one or a combination of lithium chloride, calcium chloride, or calcium hydroxide. The solvent for the aramid solution is one or a combination of dimethyl sulfoxide, N-methylpyrrolidone, or dimethyl phthalate.
4. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution is 1-10 wt%.
5. The preparation process of the high-permeability aramid-coated separator according to claim 4, characterized in that: The degree of alcoholysis of the polyvinyl alcohol is 99%.
6. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The solvent for polyvinyl alcohol is dimethyl sulfoxide.
7. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The defoamer is one or a combination of diethylhexanol, n-octanol, isooctanol, or isoamyl alcohol.
8. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The adhesive is a polyacrylic resin, polyvinyl acetate, or ethylene-vinyl acetate copolymer.
9. The preparation process of the high-permeability aramid-coated separator according to claim 1, characterized in that: The diaphragm is a polyethylene diaphragm, a polypropylene diaphragm, or a polyamide diaphragm.
10. A highly permeable aramid-coated separator, characterized in that: It is prepared by any one of the preparation processes described in claims 1-9.
Citation Information
Patent Citations
Aramid coated lithium ion battery diaphragm and preparation method thereof
CN104993089A
Aramid fiber coated lithium ion battery diaphragm
CN109830632A